The Effect of Government Support Policies on the Export of Iranian Food Industry Products Using the System Dynamics-Agent Base Approch - Eidizadeh, Shahram; Mohammadi, Hossein; Kohansal, Mohammadreza (International Journal of Psychosocial Rehabilitation, 2025)
Theoretically, increase in the export rates could improve economic growth. Therefore, export development, as one of the strategies of economic development, is the main determinant in order to increase production capacity, employment, and provide foreign exchange earnings for investment in new technologies. On the other hand, achieving a high economic growth rate is the economic goal of all countries, which guarantees the implementation of appropriate economic policies, especially government support policies in the field of tax, subsidy, consumption, production and global trade policies. Iran's position in the food industry, given the high potential in this field in the country, has caused it not to have a proper position in the huge food market and international trade. Therefore, in this study, the effect of government support policies on the export of Iranian food industry products has been investigated using the system dynamics-agent base approach. After designing causal- Loop diagrams and Stock-flow, the equations are written and simulation model for the period of 2017-2035 were performed. The results of the simulation showed that with the continuation of the current trend and the lack of change in conditions, the export of Iranian food industry products in the last year of the simulation (2035) will not be significant and will be only 3.8 billion dollars. In the following scenario, it was assumed that if the government's supportive policies to help export food industry products experience growth and improvement conditions (policies such as customs, tax, production, etc.), in these circumstances, food industry exports are expected to increase by $1.2 billion compared to the base model. In other words, improving government policies will make the export of food industry products reach $ 5 billion by the end of the simulation year (2035). The variable of efficient government policies is also considered as a factor in this research. If it is assumed that the efficiency index of government policies changes behavior and takes an upward trend, the export of Iranian food products will be established to 5.3 in the final year of simulation in the system dynamics-Agent base model.